A method of dynamic homogenization: application to 2D core calculation. (February 2021) - Galia, Antonio; Sanchez, Richard; Zmijarevic, Igor
Highlights: Development of a new dynamic homogenization approach for core calculations.. Equivalence and Flux Discontinuity Ratios applied to RHPs with surface leakage. We tested the methodology on a PWR MOX/UOX heterogeneous 2D configuration. Abstract: Three-dimensional deterministic core calculations are typically based on the classical two-step approach, where the homogenized cross sections of an assembly type are precalculated and then interpolated to the actual state in the core. On the other hand, 3D direct transport calculations and the 2D/1D Fusion method have recently been applied showing excellent agreement with reference Monte-Carlo, but still remaining computationally expensive for multiphysics applications and core depletion calculations. In the present work, we propose a method of Dynamic Homogenization (DH) as an alternative technique that lies between the classical and the direct approaches in terms of accuracy and performance, with no need of off-line calculations and avoiding expensive 3D transport calculations. The method consists in an iterative process between core and assembly calculations, whose main feature is to homogenize the cross sections taking into account the environment of each assembly. To do that, we define a reference homogenization problem that is solved with imposed core eigenvalue and fixed incoming boundary source and that is normalized to the core macro-currents. We have also analyzed the equivalence theory and flux discontinuity ratios techniques in the framework of non-conservative boundary conditions because particular care has to be taken in this case in order to preserve the total net assembly leakage. The current work presents analysis and tests of the Dynamic Homogenization technique for two-dimensional configurations. The NEA "PWR MOX/UO2 Core Transient Benchmark" was chosen to perform the calculations and compare the different methods.